Definitive identification of Ordovician-sourced oils in the Tarim Basin: geochemical constraints from biomarkers and sulfur isotopes - Daowei Wang; Chunfang Cai; Haijun Yang; Zicheng Cao; Qinghua Wang; Hao Zhang; Peng Sun; Weiquan Zhao; Wei Wang; Zhengzhong Liang; Haoyu Zhang; Qinghua Zheng (Organic Geochemistry, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Vessel Safety Navigation Under the Influence of Antarctic Sea Ice - Weipeng Liu; Daowei Yan; Zekun Peng; Maohong Xie; Yanglong Sun (Journal of Marine Science and Engineering, 2025)
Antarctic navigation encounters substantial challenges due to the dynamic and perilous characteristics of sea ice, which pose threats to vessel safety and operational efficiency. Existing risk assessment methodologies frequently lack real-time adaptability, while strategies for icebreaker convoys remain insufficiently quantified. To address these deficiencies, this study introduces an integrated framework that combines satellite-based sea ice monitoring, operational risk prediction, and icebreaker escort optimization. First, polar research routes and hydrographic conditions are systematically analyzed to enhance navigation planning. Second, a risk assessment system is developed by leveraging satellite-derived sea ice density and thickness data, facilitating a near-real-time hazard assessment (subject to satellite data latency) evaluation with 96.3% accuracy in ice type classification and a 15% improvement in risk prediction precision compared to conventional methods. Finally, kinematic safety criteria for icebreaker-escorted convoys are established, specifying speed-dependent distance thresholds to minimize collision risks, achieving optimal speeds of 1.4–2.3 knots for PC3-class vessels and 10–20% speed improvements for escorted vessels in cleared channels. The findings offer actionable insights into polar route optimization, risk mitigation, and safe ice navigation protocols, thereby directly supporting operational decision making in Antarctic waters.

Unraveling the origin and charge of Halahatang oils, Tarim Basin - Peng Sun; Chunfang Cai; Daowei Wang; Yu Qi; Chenlu Xu; Paul F. Greenwood (Organic Geochemistry, 2025)

Robust Optimization under Geological Uncertainty Using a TransUNet-Based Surrogate Model with EnOpt Algorithm - Jianqiao Liu; Daowei Zhang; Jia Liu; Wenyue Sun; Huanquan Pan; Yiheng Zhu; Hongbin Jing; Zhengbao Fang (Mathematical Geosciences, 2025)

Hazard and pollution characteristics of rock-containing dust in coal mine tunneling faces based on experimental and numerical study - Banghao Zhou; Botao Qin; Qun Zhou; Jian Gan; Zhipeng Deng; Fujun Zhao; Mei Ran; Daowei Sun (Process Safety and Environmental Protection, 2024)

Construction and application of a novel WGAN-CNN-based predicting approach for dust concentration at underground coal mine working faces - Banghao Zhou; Botao Qin; Qun Zhou; Daowei Sun; Pengpeng Chen; Kai Yang; Qingyan Pan; Huizhen Li (Environmental Science and Pollution Research, 2024)

Reconfiguring oxygenation at ∼1.4 Ga: New constraints as informed by the ancient oceanic sulfur cycle - Ziwen Jiang; Chunfang Cai; Christopher J. Tino; Daowei Wang; Yu Qi; Peng Sun; Yanyan Peng; Yongjie Hu; Dawei Liu; Tianyuan Wei; Lei Jiang (Global and Planetary Change, 2024)

Controls on petroleum stability in deep and hot reservoirs: A case study from the Tarim Basin - Daowei Wang; Chunfang Cai; Lu Yun; Jingyan Liu; Peng Sun; Ziwen Jiang; Yanyan Peng; Hao Zhang; Tianyuan Wei; Bingbing Pei (Marine and Petroleum Geology, 2023)

Climate change and Australia’s primary industries: factors hampering an effective and coordinated response - Rebecca Olive Darbyshire; Stephen B. Johnson; Muhuddin Rajin Anwar; Forough Ataollahi; David Burch; Curtis Champion; Melinda A. Coleman; James Lawson; Sarah E. McDonald; Michelle Miller; Jianhua Mo; Mary Timms; et al. (International Journal of Biometeorology, 2022)

Geochemical characteristics of carbonate rocks in a salinized lacustrine basin: a case study from Oligocene formation in the Qaidam Basin, northwestern China - Qilin Chen; Daowei Zhang; Jiangong Wang; Fan Zhao; Yingru Liu; Zhenggang Zhang; Xiujian Sun; Chenggang Huang; Yadong Bai (Carbonates and Evaporites, 2020)

Distinctive role of ACVR1 in dentin formation: requirement for dentin thickness in molars and prevention of osteodentin formation in incisors of mice - Xue Zhang; Ce Shi; Huan Zhao; Yijun Zhou; Yue Hu; Guangxing Yan; Cangwei Liu; Daowei Li; Xinqing Hao; Yuji Mishina; Qilin Liu; Hongchen Sun (Journal of Molecular Histology, 2019)

The best salt solution parameter to describe seed/seedling responses to saline and sodic salts - Hongxiang Zhang; Yu Tian; Bo Guan; Daowei Zhou; Zewei Sun; Carol C. Baskin (Plant and Soil, 2018)

A systemic analysis of typhoon risk across China - Xinliang Xu; Daowei Sun; Tengjiao Guo (Natural Hazards, 2015)

Potential of Mesenchymal Stem Cells by Adenovirus-Mediated Erythropoietin Gene Therapy Approaches for Bone Defect - Chen Li; Jian Ding; Liming Jiang; Ce Shi; Shilei Ni; Han Jin; Daowei Li; Hongchen Sun (Cell Biochemistry and Biophysics, 2014)

Evolution and spatial patterns of spheres of urban influence in China - Kaiyong Wang; Yu Deng; Daowei Sun; Tao Song (Chinese Geographical Science, 2014)

Timber Harvesting Margins in the Southern United States: A Temporal and Spatial Analysis - Changyou Sun; Daowei Zhang (Forest Science, 2006)
This study focuses on the logging sector by analyzing timber harvesting margins in the southern United States between 1977 and 2001. The real growth rate of harvesting margins has been negative for pine pulpwood, while positive for pine sawtimber, hardwood pulpwood, and hardwood sawtimber. Harvesting margins for pulpwood are more stable over time and more integrated spatially when compared with those for sawtimber. There is no perfect integration in the logging sector by timber product and no individual state is found to lead the logging service market. The revealed patterns are explained in terms of changing demand for forest products and forest industry structure.

The Effects of Exchange Rate Volatility on U.S. Forest Commodities Exports - Changyou Sun; Daowei Zhang (Forest Science, 2003)
This article addresses the impact of exchange rate volatility on U.S. exports of four forest commodities. Exchange rate volatility is measured by the standard deviation of the growth rate of real effective exchange rate of the U.S. dollar. The nonstationarity of individual time series is explicitly taken into account by employing multivariate cointegration analysis and error correction models. The results show that exchange rate volatility has a negative impact on U.S. exports in the long term, but short-term dynamics vary for different commodities. A stable currency policy in the long run helps promote U.S. exports of forest commodities, although some commodities may benefit from exchange rate volatility in the short term.

Forest Resources, Government Policy, and Investment Location Decisions of the Forest Products Industry in the Southern United States - Changyou Sun; Daowei Zhang (Forest Science, 2001)
In this article, the results of an initial attempt to estimate the effects of state attributes on plant location and investment expenditure were presented for the forest products industry in the southern United States. A conditional logit model was used to analyze new plant births, and a time-series cross-section model to assess the total capital expenditure. Significant positive effects were found for personal income and forest inventory, and negative effects were found for population density. In the short run, tax and energy costs had negative impacts on new plant births in a state, while in the long run, stumpage price and environmental stringency had negative effects on the capital expenditure. Sensitivity of model specification was documented, and policy implications were discussed. For. Sci. 47(2):169–177.